Analisis Rasio Kesehatan Kinerja Keuangan pada Koppontren Al Mubarok Lekok Kabupaten Pasuruan - Abdussalam Abdussalam (Indo Publishing, 2026)
This study aims to examine the financial health ratios of Koppontren Al Mubarok, Lekok District, Pasuruan Regency. The research employed a quantitative method with a descriptive approach. Secondary data were utilized as the primary data source, collected through documentation techniques by examining the financial statement records of Koppontren Al Mubarok Lekok. The analytical method applied consisted of financial performance health ratio analysis, encompassing liquidity ratios, solvability ratios, efficiency ratios, and profitability ratios. The findings indicate that the overall financial health ratios of Koppontren Al Mubarok Lekok fall within the poor category. This is evidenced by the liquidity ratios — comprising the Current Ratio and Cash Ratio — and the solvability ratios — comprising the Debt-to-Equity Ratio (DER) and Debt-to-Asset Ratio (DAR) — which, based on the five-year average from 2018 to 2022, consistently remained within the poor or unhealthy category. In contrast, the efficiency ratio (BOPO/Operating Expense-to-Operating Income Ratio) and the profitability ratios — comprising the Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) — were classified within the excellent category, as measured against the standards stipulated in the Regulation of the Minister of Cooperatives and Small and Medium Enterprises No. 06/Per/M.KUKM/V/2006.